THE USE OF AUDITORY, INTELLECTUALLY, REPETITION MODEL WITH MULTIMEDIA TO IMPROVE MATCH LEARNING AT THE FOURTH GRADE STUDENTS OF SDN 5 KUTOSARI IN THE ACADEMIC YEAR OF 2014/2015 - Triani, Desi (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Use of Auditory, Intellectually, Repetition Model with Multimedia to Improve Match Learning at the Fourth Grade Students of SDN 5 Kutosari In The Academic Year of 2014/2015. The objectives of this research are to describe the application of Auditory, Intellectually, Repetition (AIR) model with multimedia, to describe improve math learning, and to describe the problems and solutions. This research is a collaborative classroom action research which is conducted in three cycles, each cycle consist of planning, acting, observing, and reflecting.  The  subjects of the research were the 31 students of the fourth grade of SDN 5 Kutosari. The results of the  research is in the first cycles can reach 71%, in second cycles is 87,1%,  and third cycles is 96,8%. That show the use of AIR  model with multimedia can improve math learning for the fourth grade students of SDN 5 Kutosari in the academic year of 2014/2015. Keywords : AIR, multimedia, Mathematics